Concomitant nexus assessment between the environment and health of wildlife in Hwange urban green spaces - Martha Jena; Beaven Utete (Sustainable Environment)
Urban green spaces (UGS) mitigate negative impacts of urban living and provide positive effects on citizens’ mood, health and well-being. The net effect of UGS on wildlife health and human welfare remains understudied in urban zones proximal to wildlife rich areas. This study assessed the concomitant relationship between the environment and health of wildlife in Hwange Town in Zimbabwe through a questionnaire survey from June—December 2022. This study aimed to: i) assess the local perceptions on the link between urban ecology and urban ecosystems relative to wildlife health, ii) determine the local perceptions on the changes in the areal extent of green spaces, and iii) examine local perceptions towards green spaces and human-wildlife conflict in Hwange Town. Locals indicated that agricultural activities, urbanisation, mining and poaching were destroying and polluting the natural habitat. Increased magnitude, impact and frequency of wildlife-human conflicts signals increasing depletion of green spaces and expansion of urbanisation into wildlife habitats. There was no statistically significant correlation (r = 0.088; p = 0.172) in the local perceptions on the relation between ecosystem and well-being of wildlife. The urban ecosystem mosaic complex is unpredictable, heterogenous and evolving with human activities imploring a need for optimisation of human-activities and wildlife wellbeing. However, without financial and infrastructural support local communities are unable to conserve wildlife. We suggest community-based wildlife protection programmes integrating citizen science data (local ecological knowledge) using existing information communication platforms as alternative options to sustain wildlife conservation in urban green spaces in wildlife rich developing towns.